Религия и этнос: грани формирования французского менталитета - Чернышева, А.С. (Культура народов Причерноморья, 2013)
В статті аналізується вплив католицької церкви на формування французького національного
характеру. Досліджується та узагальнюється філософський, соціологічний і релігієзнавчий матеріал
про етнічну та соціокультурну самобутність французького народу, а релігійні цінності розглянуті в
якості вирішального чинника духовно-культурної сфери, що вплинув на формування духовного архетипу і
соціальних норм французького суспільства. В статье анализируется влияние католической церкви на формирование французского
национального характера. Исследуется и обобщается философский, социологический и
религиоведческий материал об этнической и социокультурной самобытности французского народа, а
религиозные ценности рассматриваются в качестве решающего фактора духовно-культурной сферы,
оказавшего влияние на формирование духовного архетипа и социальных норм французского общества. The influence of the Catholic church upon the formation of the French national character is being
analyzed in the article. Philosophic, sociological and religious material about the ethnic and sociocultural
originality of the French people is investigated and generalized in the article. Religious values are represented
as the decisive factor of the spiritual cultural sphere, which influenced the formation of social norms of the
French society. The object of investigation is the French ethnic mentality and its features. The influence of the
Catholic denomination upon the formation of the spiritual archetype of the given ethnos and the instruments with
the help of which Christian senses had been produced into the sphere of human being are analyzed in the article.
The attention is paid to the mutual influence of confessional and ethnic elements that led to the formation of the
specific peculiarities of the French Catholicism with vividly expressed satisfactional thinking, rationalism,
anthropocentrism, which found their reflection in the model of social hierarchy. The process of change of the
ethnoconfessional identity of the French people during the long historical period since the Early Middle Ages till
our days is being traced in the article.